A Pilot Study of the Impact of Double-Dose Robust Vocabulary Instruction on Children's Vocabulary Growth. Issue 2 (2nd April 2016) - ,; Arthur, Ann M.; Davis, Dawn L.
ABSTRACT: Double-dose instruction, in which instructional lessons are supplemented to provide additional instructional time, is a mechanism used in some schools for boosting outcomes in certain academic areas. The purpose of this study was to examine the effects of double-dose vocabulary instruction, relative to single-dose and business-as-usual control instruction, for pre-kindergarteners through third-graders in a quasi-experimental pilot study; the vocabulary instruction was embedded in a more broadly focused language-comprehension intervention. Pretest, posttest, and measures of targeted vocabulary were collected over a 21-week period of implementation to investigate children's vocabulary development during the intervention. In general, single- and double-dose instruction resulted in equivalent effects on children's learning of targeted vocabulary, although effect-size estimates were always larger for the double-doses condition relative to single dose. Both were superior to the business-as-usual instruction, with effect-size estimates similar to that seen in the vocabulary-intervention literature. The results of this pilot study suggest that increased instructional time devoted to vocabulary development only may not provide enhanced outcomes for some students, and thus may not be a worthwhile investment of school resources compared to other language-based instruction.